Anxiety, depression, type D personality, somatosensory amplification levels and childhood traumas in patients with panic disorders - Taşdelen, Yasin; Yağcı, İbrahim (Journal of Surgery and Medicine, 2019)
Aim: Persons with type D personality have been shown to be predisposed to depression and anxiety disorders. However, to our knowledge, there are no studies which have investigated the relationship between panic disorder (PD) and type D personality. Our aim in the current study was to determine whether PD was associated with Type D personality, anxiety, depression, childhood trauma and somatosensory amplification by comparing the characteristics of patients with and without PD. Methods: We designed a questionnaire based case-control study. The study group included 100 patients with panic disorder, and control group consisted of 100 healthy individuals. Sociodemographic Data Form, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Type D Personality Scale (DS14), Childhood Trauma Questionnaire (CTQ) and Somatosensory Amplification Scale (SSAS) were carried out for each participant. Results: The patient and control groups were found to be similar in terms of sex, marriage status, education status and employment status. Compared to the control group, scores for BAI (P<0.01), BDI (P<0.01), CTQ (P<0.01), DS-14 (P<0.01) were found to be significantly higher in the patient group. The frequency of Type D personality was also higher in the patient group. Conclusion: Our findings show that patients with PD have significantly higher scores in anxiety, depression, Type D Personality, CTQ total scores measures compared to controls. We did not find any associations between PD and somatosensory amplification. We believe our findings will contribute significantly to the limited literature on this topic.